Assessment of hematological parameters after laparoscopic appendectomy using conventional procedures on rats (VETERINARIA, 2020)
The aim of this study study was to asses the hematological status of rats after laparoscopic appendectomy, using Endoloop ligature-Vicryl and Hem-o-lok clips. Seventy rats were randomized into three groups. The first group consisted of the endoloop-treated, Vicryl, 30 rats. The second group was made up of 30 rats whose appendix base was Hem-o-lock plastic cliptreated. The third group of 10 rats represented the control group. In group I the blind part of the caecum was ligated with Vicryl ligature. In group II, Hem-o-lok was applied to the blind part of the caecum, while the distal part was resected. Ten animals from each experimental group were drawn peripheral blood from the caudal vein three times; on the 7th, 28th and 60th postoperative day. Rats from the control group (n = 10) were drawn blood only once and used for comparison. Blood was taken from the animals to obtain a complete blood sample. The following hematological parameters were analysed: HGB, HCT, MCV, MCH, MCHC, RBC and WBC. A microscopic analysis of the poikilocytotic blood corpuscles was performed. LYM, NEU, MON, BAS and ACI were differentiated and numbers were presented in percentages after the analysis of 1000 of them in each animal. Statistically significant difference between almost all of the investigated hematological parameters, except MCH and WBC count, was detected. Leukocyte cells responded equally to the resorptive suture and the plastic Hemo-lok clip in terms of neutrophilia, leukopenia and monocytosis. Results of the present study indicate a mild occurrence of hypochromic anemia in certain postoperative time periods, with the appearance of erythrocyte poikilocytic forms, suitable for this type of anemia, in both experimental groups.
Keywords: Hypochromic anemia; Hem-o- lok clips; anulocytes; spherocytes; Endoloop ligature-Vicryl